(untitled) (El-Wahat Journal for Research and Studies, 2026)
This article aims to explore the representations of travel discourse within the genre of maqama, taking the Baghdad Maqama by Ibn Mihraz al-Wahrani as a case study. The maqama is a narrative genre capable of incorporating various literary genres. The features of travel are clearly manifested in al-Wahrani’s maqama through the use of travel art characteristics such as narration, description, and the employment of the first-person pronoun (individual “I”), in addition to the diverse information contained within the maqama. The study concludes that the author, Ibn Mihraz al-Wahrani, successfully blended the genres of travel and maqama by drawing on the unique elements of each literary form.